Exploring the Nature of Undergraduates’ Peer Collaboration in a PBL Writing Process - Aliyu, Muhammad Mukhtar (International Journal of Language Education, 2020)
Despite the importance of writing skills to academic success, many undergraduates face a lot of challenges with writing in English. Studies have shown that engaging and supporting students in a writing process help to improve the students’ writing performance. Therefore, this study used a Problem-based learning approach (PBL) in order to give students opportunities to be engaged and support one another in a writing process through face-to-face interactions. The paper specifically reports what the students do to support their peer in the PBL writing process. An intact class of 18 second-year students in an English Composition course in Nigeria was selected to participate in the study. Data were obtained through audio- and video-recording of the students’ face-to-face interactions. The findings showed that the participants supported theirs peer through various ways in the PBL process such as modelling their facilitators, sharing tasks and responsibilities, clarifying instructions and unclear terms, using dictionary, suggesting other sources to get more information, checking for consensus, creating humour, encouraging others to participate and raise their voices while speaking, restating time given to a session and giving overview of a previous session. The support provided by the peers helped the students to improve their writing. The study has some implications for writing teachers.